Experimental Study on Kaiser Effect of Reinforced Concrete Simply-Supported Beams - Yongfeng Xu; Hailong Wang; Tengfei He; Jiajun Ma; Pengfei Zhao; Anquan Ji; Lei Liu; Yang Liu (Tehnički Vjesnik, 2023)
With the progress of transportation, an increasing number of bridges are put into operation, and the assessment of bridge bearing capacity is considered a significant measure to ensure bridge safety. As a critical approach for structural monitoring, acoustic emission is widely used in engineering projects. Since the Kaiser effect is an important phenomenon in acoustic emission, it is necessary to explore the Kaiser effect of reinforced concrete structures and the determination method of the Kaiser point. In this thesis, four reinforced concrete simply supported beams were utilized for the graded loading experiment under bending loads. After accumulating acoustic emission parameters, Kaiser point was selected for preliminary evaluation. Taking Kaiser point as the midpoint, the appropriate interval was determined. According to the continuity criterion of acoustic emission signals and the quadratic fitting curve based on experimental data, the Kaiser point was corrected by following the average growth rate of acoustic emission parameters. These simply supported beams were classified into two groups. One group was used to explore the acoustic emission characteristics when the load was less than the historical maximum, while the other group was used to analyze changes in the Kaiser effect with increasing load. Finally, based on the results of the specimen inspection, the influence of initial damage on the Kaiser effect was analyzed. The research results alleviated the influence of human factors on the determination of the Kaiser point and can serve as the theoretical basis for damage monitoring based on the Kaiser effect and bearing capacity evaluation of reinforced concrete structures.